Medicinal Animals and Plants as Alternative and Complementary Medicine in Southern Regions of Khyber Pakhtunkhwa, Pakistan - Mussarat, Sakina; Ali, Rehman; Ali, Shandana; Mothana, Ramzi A.; Ullah, Riaz; Adnan, Muhammad (Frontiers in Pharmacology, 2021)
Background: Traditional therapies, by using plants and animals, are very common practices in local communities. This study was aimed to document animals and animal-plant combinations analyzed by quantitative indices that are used as alternative practices for curing acute to chronic ailments in the study area. Methods: The data were collected (2017-2018) in three remote areas (Dera Ismail Khan, Bannu, and Lakki Marwat) through questionnaire and face-to-face interview from local inhabitants. Data on ethnomedicinal uses and cultural values of animal’s products or parts and their mixture with plants were analyzed using various indices such as frequency of citation (FC), Informant Consensus (FIC) and fidelity level (FL) to find the highly preferred species in the area. Results: A total of 185 informants (117 females and 68 males) were interviewed. The study documented 32 animal species, vertebrates (n=24) and invertebrates (n=8), for curing 37 types of diseases. Mammals (n=13) were among the most commonly utilized species followed by birds (n=8), arthropods (n=8), reptiles (n=20) and fishes and annelids (n=1 each). Among the reported animals, mongoose, monkey, fish, rabbit, and dove were the newly reported species used as alternative medicine. The meat of goat, monkey, and hare was used to treat chronic diseases such as hepatitis C, cancer, epilepsy, and asthma. A total of 17 plants belonging to 15 botanical families were used in combination with animal parts/products. The commonly used families were Piperaceae (31%) followed by Apiaceae (27%). The notable plant species in combinations with animal products were Curcuma longa, Piper nigrum, Coriandrum sativum, Brassica rapa, and Phoenix dactylifera. Seeds were the highest used part in animal-plant mixture recipes. Conclusion: Our findings suggest that local communities in southern regions of Khyber Pakhtunkhwa have substantial knowledge about the formulation of ethnomedicines from both fauna and flora that needs urgent documentation to avoid eroding and for conservational purposes. The newly reported phytozootherapeutic recipes and animal species can potentially be a source of pharmacologically active constituents and should be checked experimentally for further confirmation.